International trade and monopolistic competition without CES: Estimating translog gravity - Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper derives a micro-founded gravity equation in general equilibrium based on a translog demand system that allows for endogenous markups and rich substitution patterns across goods. In contrast to standard CES-based gravity equations, trade is more sensitive to trade costs if the exporting country only provides a small share of the destination country's imports. As a result, trade costs have a heterogeneous impact across country pairs, with some trade flows predicted to be zero. I test the translog gravity equation and find strong empirical support in its favor. In an application to the currency union effect, I find that a currency union is only associated with substantially higher bilateral trade if the exporting country provides a small share of the destination country's imports. For other pairs, the currency union effect is modest or indistinguishable from zero.
Keywords: F11; F12; F15; 330; translog; trade costs; gravity; currency union; monopolistic competition; trade cost elasticity; heterogeneity; zero trade; Außenwirtschaft; Kosten; Gravitationsmodell; Mikroökonomische Fundierung; Monopolistischer Wettbewerb; Allgemeines Gleichgewicht; Währungsunion; Schätzung; OECD-Staaten